(untitled) (Sebha University Conference Proceedings, 2024)
Balanites aegyptiaca (L)Del is one of the plants used in food and medicinal preparations. Heglig is commonly used to treat many different diseases such as fever, malaria, wounds, constipation, hemorrhoids, stomach disorders, intestinal worm infections, epilepsy, diarrhea, constipation, dysentery, syphilis, and asthma. Objective of the study: This study aims to investigate the medical and nutritional importance of the heglig plant, and to evaluate the content of some chemical compounds and the biological effectiveness of the heglig date extract, and to know its effect on some types of bacteria. Results: The active ingredients of the aqueous and methanolic extract of the heglig dates (Balanites aegyptiaca Del) were studied, and their effect on two types of Gram-positive bacteria, Bacillus subtilis and Stahylococcus aureus, and two types of Gram-negative bacteria, Escherichia coli and Pseudomonas aeruginosa, were studied. Both extracts were found to contain proteins, tannins, phenols, saponins, terpenes, steroids, and glycosides, but did not contain starch or anthocyanins. The presence of racin and flavonoids was noted in the aqueous extract but not in the methanolic extract. The amount of saponins, phenols, and flavonoids was also determined. The results of testing the effectiveness of the aqueous and methanolic extract of Heglig dates at different concentrations of 100, 200, 400, 600, and 800 mg/ml using the disk diffusion method showed that the aqueous extract of all concentrations used has inhibitory activity on P. aeruginosa bacteria for all concentrations used as well as S. aureus at a concentration of 800 mg/ml, and the rest of the E.coli and B. subtilis bacteria showed a pattern of resistance to different concentrations. As for the methanolic extract, it showed effectiveness in inhibiting P. aeruginosa bacteria for concentrations of 200, 400, and 600 mg/ml, and it was resistant to concentrations of 100, 800 mg/ml, and no effect was shown on the bacteria E.coli, S.aureus, and B. subtilis. For all concentrations used for the alcoholic extract of Heglig fruits.